(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
Studies on landfill containment, which support structures like a railroad, still have restricted alternatives in Brazil. In 2016, in the state of Pará/ Brazil, the construction of a railway was completed. In the following year, cracks were observed on the crest of the embankment slope. The objective was to evaluate, based on geotechnical investigation, the best engineering solution to contain the instability of the slope under study, through a containment solution. From this study, to cover stability, a retaining wall can be built as a solution, which represents the best cost of implementation and maintenance during the useful life of the asset. It is also suggested that periodic technical inspections be carried out on the surface of the access road and on the sides of the railway platform.